A microepidemiologcal study of malaria in southern Sri Lanka, including aspects of clinical disease and immunity - Gunawardana, D. M. (Faculty of Medicine, University of Colombo, 1998)
The study investigated over a period of 18 months, the clinical disease and micro epidemiology of malaria in a population living in an endemic area in Southern Sri Lanka. It examined the acquisition of clinical immunity to natural malarial infections induced by both species of malarial parasites, P.vivax and P.falciparam, in relation to the hamologous as well as the heterologous species. It also led to the identificaton of risk factors for the acquisition of malaria and revealed new information on the clinical nature of malarial inc-fections. 1944 residents in 423 houses in villages in Monaragala Dostroict were examined.
A thesis submitted the University of Colombo (Faculty of Medicine) the degree of Doctor of Philosophy
Keywords: Malaria-epidemiology; Malaria-immunology; MALARIA